LIQUID CRYSTAL DISPLAY DEVICE - TANAKA YASUHARU; HISATAKE YUZO; YAMADA YUMIKO (1994)
PURPOSE:To obtain a liquid crystal display device in which the non-uniformity or lowering of a contrast ratio can be prevented from occuring even when it is displayed for a long time and satisfactory display characteristic with a wide visual angle and high contrast can be obtained. CONSTITUTION:A lateral electric field electrode 15 is arranged adjacently to one side 14a of an electrode 14 to form picture element electrodes 14 arranged in matrix shape in two areas A, B with different tilting directions of a liquid crystal molecule, and reverse tilt is generated by a lateral electric field at a part of the area for normal tilt decided by the orientation of orientation film 19, 23. The boundary of different tilt areas can be decided by an auxiliary capacitor (Cs) line 16 which bisects the picture element electrode.